Deciphering the Role of Selenoprotein M - Lance G. A. Nunes; Antavius Cain; Cody Comyns; Peter R. Hoffmann; Natalie Krahn (MDPI AG, 2023)
Selenocysteine (Sec), the 21st amino acid, is structurally similar to cysteine but with a sulfur to selenium replacement. This single change retains many of the chemical properties of cysteine but often with enhanced catalytic and redox activity. Incorporation of Sec into proteins is unique, requiring additional translation factors and multiple steps to insert Sec at stop (UGA) codons. These Sec-containing proteins (selenoproteins) are found in all three domains of life where they often are involved in cellular homeostasis (e.g., reducing reactive oxygen species). The essential role of selenoproteins in humans requires us to maintain appropriate levels of selenium, the precursor for Sec, in our diet. Too much selenium is also problematic due to its toxic effects. Deciphering the role of Sec in selenoproteins is challenging for many reasons, one of which is due to their complicated biosynthesis pathway. However, clever strategies are surfacing to overcome this and facilitate production of selenoproteins. Here, we focus on one of the 25 human selenoproteins, selenoprotein M (SELENOM), which has wide-spread expression throughout our tissues. Its thioredoxin motif suggests oxidoreductase function; however, its mechanism and functional role(s) are still being uncovered. Furthermore, the connection of both high and low expression levels of SELENOM to separate diseases emphasizes the medical application for studying the role of Sec in this protein. In this review, we aim to decipher the role of SELENOM through detailing and connecting current evidence. With multiple proposed functions in diverse tissues, continued research is still necessary to fully unveil the role of SELENOM.